Abscess of the right iliopsoas muscle: rare disease and difficulties in its diagnosis - S. V. Stolov; M. Yu. Kabanov; K. V. Semencov; T. Yu. Yamshchikova; O. V. Makarova; E. M. Ugleva (Вестник хирургии имени И.И. Грекова)
The article presents the clinical case of an abscess of the iliopsoas muscle (iliopsoitis), a rare abdominal infectious and inflammatory disease that required a multidisciplinary approach in the diagnosis of this pathology in a multidisciplinary hospital.